Challenges of Water Resource Development and Management in Zing Town, Taraba State, Nigeria - Oruonye, E D; Bange, E (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
This study examined the challenges of water resource development and management in Zing town,Taraba State, Nigeria. The study considered issues of sources of water supply in Zing town, the nature of water challenges, impacts of the water challenges on the socio-economic life of the people, water management strategies and prospect of urban water resource development in the study area. 110 questionnaires were systematically administered in ten streets that were purposively selected in Zing town. The data were analyzed using descriptive statistics. The result of the finding indicates that majority (45.5%) of the respondent have their water source from borehole, 18.2% streams, 18.2% hand dug wells and 9.1% from other sources (mostly water vendors). The study shows that 68.2% of the respondents had their water point located outside their households, while only 31.8% claimed to have their water sources located within their compounds (this is mostly hand dug wells). The nature of water challenge in the area ranges from severe (50%), not severe (27.3%) and normal (22.7%). The results also shows that only 34% of respondents claimed to have access to sufficient water daily, while 66% of the respondents hardly have access to sufficient water on daily basis. The study shows that the water management strategy adopted mostly by the respondent ranges from storing water in large container (48.2%), reduce water use (29.1%), increase amount spent on water (13.6%) and others 9.1% (mainly re-use of water). The prospect of water resource development in the study area is very bright with the proposal of a small earth dam in Monkin settlement by the Federal Government of Nigeria. The Monkin small earth dam which is meant to generate 500KW of electricity can be integrated into an urban water supply project in the area. This will assure more reliable water supply all year round. It will also help to overcome some of the challenges of servicing the hand pumps which rendered them inadequate when they break down. This study recommends the need to replace the old and obsolete borehole equipment with new ones and increase the number of boreholes to meet the increasing water demand in the area.